IMPLEMENTASI MANAJEMEN PENDIDIKAN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM - Sukirman Sukirman; Egal Rismasita; Leny Marlina; Asri Karolina (MANAJEMEN, 2024)
School-based management embodies a forward-thinking model in the development of educational systems, emphasizing institutional independence and creative approaches. This management framework can be viewed as a system that grants greater autonomy to educational institutions and fosters cooperative decision-making among all stakeholders (such as educators, students, administrators, support personnel, guardians, and the local community) to enhance the quality of education in line with national educational goals. This study is a qualitative field investigation, utilizing a methodology pertinent to the primary variables under examination, particularly a qualitative perspective. To gather information, researchers utilized techniques including observation, interviews, and document analysis. Results show that the application of school-based management in enhancing the quality of Islamic Religious Education in schools is generally effective, though not entirely optimal, particularly concerning the management of facilities and infrastructure. This indicates that the execution of school leadership is done effectively and efficiently. The effectiveness of school management rooted in administration relies on the presence of competent human resources, adequate financial backing, sufficient facilities and infrastructure, along with active involvement from the community (parents).